2023
DOI: 10.1021/acs.orglett.2c04318
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Deficient Fluoroarene-Mediated Synthesis of Trifluoromethyl Ketones from Carboxylic Acids

Abstract: Fluoroarene-mediated trifluoromethylation of carboxylic acids for the synthesis of trifluoromethyl ketones is disclosed. The fluoroarene activates the acid group and generates the fluoride source in situ for the trifluoromethylation reaction. The present protocol is safe and metal-free, operates under mild reaction conditions, and does not require any external additives to generate trifluoromethyl anion. The current transformation provides good functional group tolerance and also delivers 92% and 88% yields of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…In 2023, Said and Gajbhiye et al reported the fluoroarenemediated batch synthesis of trifluoromethyl ketones from carboxylic acids using Me 3 SiCF 3 (Figure 27). [42] They found that 3,4,5,6-tetrafluorophthalonitrile (TFPN) acts as an efficient activator of carboxylic acid and a fluoride source to activate Me 3 SiCF 3 . A series of carboxylic acids was converted to the corresponding trifluoromethyl ketones in high yields in the presence of Me 3 SiCF 3 , TFPN, and Et 3 N at 60 °C.…”
Section: Ruppert-prakash Reagent (Me 3 Sicf 3 )mentioning
confidence: 99%
“…In 2023, Said and Gajbhiye et al reported the fluoroarenemediated batch synthesis of trifluoromethyl ketones from carboxylic acids using Me 3 SiCF 3 (Figure 27). [42] They found that 3,4,5,6-tetrafluorophthalonitrile (TFPN) acts as an efficient activator of carboxylic acid and a fluoride source to activate Me 3 SiCF 3 . A series of carboxylic acids was converted to the corresponding trifluoromethyl ketones in high yields in the presence of Me 3 SiCF 3 , TFPN, and Et 3 N at 60 °C.…”
Section: Ruppert-prakash Reagent (Me 3 Sicf 3 )mentioning
confidence: 99%
“…Carboxylic acids and their derivatives have been converted readily into trifluoromethyl ketones 15 by using various ''CF 3 '' sources such as CF 3 CO 2 Na, 30 AgCF 3 , 31 TMSCF 3 , [32][33][34][35] or fluoroform 36,37 (Scheme 1, eqn (1)). Despite these advances, only a few methods are reported for producing [ 11 C/ 18 F]trifluoromethyl ketones.…”
mentioning
confidence: 99%
“…Such advances would pave the way for further development of functional products . For instance, the groups of Shreeve and Yamazaki first reported the trifluoromethylation using esters as starting material (Scheme a). , Conversely, the Li, Prakash, Chen, and Gajbhiye groups employed the aryl aldehyde/carbocyclic acid to synthesize the corresponding trifluoromethyl ketones using trifluoromethyltrimethylsilane (TMSCF 3 )/bpyCu­(CF 3 ) 3 as the trifluoromethyl source, respectively (Scheme b). Subsequently, Skrydstrup and coauthors developed a novel and efficient procedure to access aryl and heteroaryl trifluoromethyl ketones by applying Pd-catalyzed carbonylation chemistry and TMSCF 3 reagent as the CF 3 source (Scheme c) . While these methods offer many advantages, they also face limitations in certain aspects, such as operation under harsh conditions, the use of transition metal catalysts, limited substrates, the requirement for specific reactants, etc.…”
mentioning
confidence: 99%